Bioluminescence Analytical Applications and Basic Biology - Suzuki, Hirobumi (Biochemistry, 2019)
This book includes reviews of molecular- and organismal-level studies in bioluminescence in order to elucidate the mechanisms behind this phenomenon. It is intended for molecular biology researchers involved in bioluminescent reactions, molecular engineering of bioluminescent sensor probes, and biomonitoring of environmental toxins.. Field researchers as well as students will also find this volume to be of interest.